Mycetoma Caused by Acremonium Species in a Patient with Chronic Granulomatous Disease - Richard Antrobus; Gabriel Wong; Julie Jones; Aarnoud Huissoon (Case Reports in Immunology)
Patients with chronic granulomatous disease are predisposed to fungal infections and are therefore routinely prescribed antifungal prophylaxis. We report a case where acremonium was responsible for causing a cutaneous infection (mycetoma) despite antifungal prophylaxis. Treatment with voriconazole was initiated and the infection gradually resolved. This case highlights the need for careful clinical follow-up and thorough investigation of patients who have a neutrophil immunodeficiency.